Substitution or Elimination
im using substitution
1. solve for variable for one of the equation
x + 3y = 9
x = 9 - 3y
2. Substitute the variable into one of the equation
3 (9-3y) - y = 7
27 - 9y - y = 7
27 - 10y = 7
-10y = 7 - 27
-10y = -20
y = 2
3. sub y = 2 into any equation to find x
3x - 2 = 7
3x = 7 -2
3x = 5
x = 5/3
X+3(2) = 9
x + 6 = 9
x = 9-6
x= 3
therefore there are two solutions x = 3 and x= 5/3
F(x)=1/4x+1
F(x)=-1/4x+1/4
F(x)=-1/4x-1/4
Answer:
Its F(x)=-1/4x-1/4
Step-by-step explanation:
just took a quiz in class
B. 14
C. 16
D. 18
Answer:
C. 16
Maaf Kalo Salah Y Maaf Ya Lama Cape Itung di